2004
DOI: 10.1186/1471-2458-4-61
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette price increase on the cigarette consumption in Taiwan: evidence from the National Health Interview Surveys on cigarette consumption

Abstract: Background: This study uses cigarette price elasticity to evaluate the effect of a new excise tax increase on cigarette consumption and to investigate responses from various types of smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
3
13
2
Order By: Relevance
“…; with educational institutions being obliged to educate children and young people about harmful effects on health if using tobacco products in all curriculum areas of regular education; at the same time imposing supervision and fi nes system for violation of the points laid out in it. One would expect that an increase in taxation of tobacco products in Croatia (the most recent in July 2004) would decrease the smoking prevalence, and this would be in accordance with strong evidence on the negative correlation of pricing and tobacco use [28][29][30][31] but our fi ndings suggest a completely different development: smoking prevalence among male and female medical students is rising despite increases in taxation. The reasons for that are not clear at all, either the cigarette prices are still not high enough, or, what would be a cause for even greater concern, the tobacco use is increasing at such a pace that the effects of the measures combating tobacco use only reduce the incidence but not the prevalence.…”
Section: Discussionsupporting
confidence: 71%
“…; with educational institutions being obliged to educate children and young people about harmful effects on health if using tobacco products in all curriculum areas of regular education; at the same time imposing supervision and fi nes system for violation of the points laid out in it. One would expect that an increase in taxation of tobacco products in Croatia (the most recent in July 2004) would decrease the smoking prevalence, and this would be in accordance with strong evidence on the negative correlation of pricing and tobacco use [28][29][30][31] but our fi ndings suggest a completely different development: smoking prevalence among male and female medical students is rising despite increases in taxation. The reasons for that are not clear at all, either the cigarette prices are still not high enough, or, what would be a cause for even greater concern, the tobacco use is increasing at such a pace that the effects of the measures combating tobacco use only reduce the incidence but not the prevalence.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we found that the overall price elasticity of demand for cigarettes was estimated at -0.4, which falls within the previously reported range of -0.3 and -0.5 (Lee et al 2004). More importantly, we further found that the cigarette price elasticity for smokers with depressive symptoms was higher than that for smokers without depressive symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…The specifications of these variables are consistent with previous studies of smoking behavior in Taiwan (e.g., Lee et al 2004). Several variables reflecting human capital (age and the education levels), monthly income, marital status, and residential locations of each respondent are included.…”
Section: Other Socio-demographic Variablessupporting
confidence: 58%
See 2 more Smart Citations